Sunflower Stem Aggregates Based Bio-Building Materials: Compression Properties and Behavior - Parmo (EMARA: Indonesian Journal of Architecture, 2025)
This study was performed to investigate the compression properties and behavior of bio-based composite materials produced with sunflower stem aggregates and gypsum plaster as the building material. The experimental cubical specimens were produced with a dry density range of 218 kg/m3 to 254 kg/m3, a binder/aggregates ratio of 2.4 : 1, and a dimension of 100 mm x 100 mm x 100 mm using untreated sunflower stem particles as bio-aggregates. The compression tests were conducted using an electromechanical universal testing machine at two different loading rates and direction tests for the manufacturing samples. The engineering results indicated that the compressive strength and modulus of elasticity of sunflower-gypsum plaster materials depend on the loading rate and direction test of the specimens. The compressive strength of the materials increased with increasing loading rates. In addition, the highest Young’s modulus is in the conducting test’s samples at 10 mm/min of loading rate and in the parallel direction test.